The Effect Of Training And Work Discipline On The Performance Of Security Units At The Class I Immigration Office - Pardamean, Johannes Nico Lambok; Wicaksono, Widhi (Pascasarjana STIE Miftahul Huda, 2025)
The purpose of this study was to determine the effect of training and work discipline on the performance of employees of the Security Unit at the Class I Special Non-TPI Immigration Office in South Jakarta. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 77 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are that training has a significant effect on employee performance, the regression equation value is Y = 20.692 + 0.899 X1, the correlation coefficient value is 0.753, meaning that the two variables have a strong relationship. The determination or contribution result is 0.567 or 56.7% while the remaining 43.3% is influenced by other factors. Hypothesis test obtained t count value> t table or (9.920> 1.992). Thus, H0 is rejected and H1 is accepted. Work discipline has a significant effect on employee performance with the value of the regression equation Y = 20.692 + 0.899 X1, the correlation coefficient value obtained is 0.753, meaning that the two variables have a strong level of relationship. The results of the determination or contribution of its influence are 0.567 or 56.7% while the remaining 43.3% is influenced by other factors. Hypothesis testing obtained a calculated t value> t table or (9.920> 1.992). Thus, H0 is rejected and H1 is accepted, Training and work discipline simultaneously have a significant effect on employee performance with the value of the regression equation Y = 21.906 + 0.617X2, the correlation coefficient value is 0.583, meaning that the two variables have a moderate level of relationship. The determination or contribution value of its influence is 0.340 or 34.0% while the remaining 66.0% is influenced by other factors. The left-hand side hypothesis test obtained a calculated t value > t table or (6.214 > 1.992). This is reinforced by obtaining a significance of 0.000 < 0.05, thus H0 is rejected and H2 is accepted.